The Ability of Kayambang (Salvinia molesta D.S Mitchell) and EcEng Gondok (Eichornis crassipies (Mart.) Solms) to Decrease the Nitrogen Degree of liquid Waste from PTPN XIII Palm Oil factory in Ngabang-West Kalimantan - Mulyono, Agus Sri; Sudilawati, Dessy (Balai Riset dan Standardisasi Industri Pontianak, 2010)
The wastewater effluent of Ngabang Palm Oil Industry in one of several industrial waste, that contains high organic substances. One of them is nitrogen (N-total). Waste water treatment of palm oil industry used ponding system today, and one of solution to treat that wastewater effluent is using aquatic weeds as biofilter action. Water hyacinth (Eichornia crassipes (Mart.) Solms) and water fern (Salvinia molesta D.S.Mitchell) known as aquatic weeds that capable to decrease in a large amount the organic and inorganic substances. The aim of this research is to study the capacity of water hyacinth and water fern in decreasing nitrogen compounds (N-total, ammonia, nitrate, nitrite, N-organic) in wastewater effluent palm oil industry based in variation of treatment and difference of exposure time. This research was carried out in green house and Biology Laboratory of Biology Programme Study, Mathematic and Science Faculty of Tanjungpura University and Testing Laboratory of Institute for Industrial Research And Standardization Pontianak, from July 1st â October 31th, 2006. This experiment was designed in Completely Randomized Factorial Design with three treatments and three replication times. The collected data analized by Annava Test and least Significance Difference (LSD) test. The result show that the treatment with combination of water hyacinth and water fern were able to decrease the N-total (92,64%); ammonia (96,47%); and nitrite (90,14%).